Navigating barriers and pathways in capacity development for knowledge mobilization: perspectives from McGill University’s Faculty of Education - Golhasany, Hamid; Harvey, Blane (Frontiers in Education, 2025)
IntroductionThis study offers a case study of capacity development for Knowledge Mobilization (KMb) within the context of McGill University’s Faculty of Education, focusing on the experiences of researchers and students engaged in KMb. Amidst increasing global demands for academic research to contribute to societal benefits, this case study evaluated the participants’ experiences of challenges and support received in doing KMb activities.MethodsThis case study followed a qualitative exploratory approach, utilizing semi-structured interviews to gather detailed insights from graduate students and faculty members within McGill University’s Department of Integrated Studies in Education (Montreal, Canada). Ten participants were selected through convenience sampling, to provide a diverse representation of experiences in engaging with KMb practices. The study’s inductive data analysis strategy allowed for a comprehensive analysis of the challenges and supports related to KMb and grounded findings in the real-world experiences and perspectives of those directly involved in KMb efforts.ResultsThe research revealed organizational challenges, including inadequate recognition of KMb efforts and insufficient institutional support, as significant barriers to effective KMb. Despite these obstacles, certain enablers, such as KMb training and supportive relationships with supervisors, highlight the potential pathways for enhancing KMb capacity. Notably, the study uncovered a discrepancy between the availability and accessibility of KMb support, pointing to the necessity of tailored, accessible capacity development strategies.DiscussionBy emphasizing the need for systemic changes and prioritizing organizational capacity development, this research contributes to a more nuanced understanding of fostering effective and inclusive KMb practices with faculties of Education and beyond.